Association between different behavioral factors and dental caries among children attending the dental clinics in a sample from Saudi Arabia - Freah L. Alshammary; Amal A. Mobarki; Nadia F. Alrashidi; Ahmed A. Madfa (BMC, 2023)
Abstract Background This study aimed to assess the association between different behavioral factors and the prevalence of dental caries among children attending the dental clinic in a sample from the Hail and Tabuk regions, Saudi Arabia. Method A cross-sectional study design was employed to determine the burden of dental caries in teeth and key associated factors among 6-12-year-old children who attended different dental clinics. The data was recruited from Hail and Tabuk districts, Saudi Arabia. The study included only Saudi nationals, whose parents could fill out the self-administered questionnaire and provide informed consent for their child's dental examination at clinics. Children underwent a simple dental examination based on the World Health Organization diagnostic criteria for oral health surveys. The Decayed, Missed, Filled Tooth (DMFT) index developed by the World Health Organization (WHO) was utilized to assess dental caries. Descriptive statistics were performed to describe categorical variables. The mean DMFT was compared between girls' and boys' and the children from Hail and Tabuk regions using the Mann-Whitney U-test. The chi-square test was used to examine the association between different behavioral factors and the prevalence of dental caries. Results Of the total 399 children examined, 203 (50.9%) were boys, whilst 196 (49.1%) were girls. The prevalence of dental caries was correlated with the cleaning tool, parental educational level, dental visits, and sugar consumption (p < 0.05). However, brushing frequency failed to demonstrate a correlation with the prevalence of dental caries (p > 0.05). The total mean DMFT for the studied sample was 7.81 (SD ± 1.9). Caries' experience was made up mainly of decayed teeth. Decayed teeth made up an average of 3.30 (SD ± 1.07). The total mean of missing and filling teeth was 2.51 (SD ± 0.99) and 1.99 (SD ± 1.26) respectively. There was no statistically significant difference in the mean DMFT and gender or between Hail and Tabuk (p < 0.05). Conclusion Saudi Arabia continues to have a high prevalence of dental caries compared to the global norm.